2020
DOI: 10.2139/ssrn.3614940
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and its Impact on Inequality of Opportunity in Psychological Distress in the UK

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 18 publications
6
57
0
Order By: Relevance
“…Results from this longitudinal analysis of incidence of CMD in the UK adult population from April to July 2020 is strongly corroborated by the repeated cross-sectional surveys from the ONS Opinions and Lifestyles survey for Great Britain, which found that levels of anxiety decreased considerably and steadily since the 20th of March 2020 from nearly half of the population to 28% on the 21 st of June (Davies, R, 2020). Furthermore, The UCL COVID-19 social study of 90,000 UK adults found that levels of anxiety and depression fell in early June as lockdown measures began to lift .…”
Section: Discussionmentioning
confidence: 54%
“…Results from this longitudinal analysis of incidence of CMD in the UK adult population from April to July 2020 is strongly corroborated by the repeated cross-sectional surveys from the ONS Opinions and Lifestyles survey for Great Britain, which found that levels of anxiety decreased considerably and steadily since the 20th of March 2020 from nearly half of the population to 28% on the 21 st of June (Davies, R, 2020). Furthermore, The UCL COVID-19 social study of 90,000 UK adults found that levels of anxiety and depression fell in early June as lockdown measures began to lift .…”
Section: Discussionmentioning
confidence: 54%
“…Age was associated with psychological distress, χ 2 (18, N = 12,407) = 762.37, p < 0.001, see Table 3. Levels of distress were least in the oldest (75+) group, with 33.8% having clinical significance and 8.0% being classified as "severe, " and greatest in the youngest group (16)(17)(18)(19)(20)(21)(22)(23)(24) with 76.6 and 36.2%, respectively. Calculation of odds ratios using the oldest group as the comparison shows that individuals with severe psychological distress are 6.50 times more likely to be in the youngest age group in comparison to the oldest age group.…”
Section: Psychological Distressmentioning
confidence: 99%
“…There are also an increasing number of yet-to-be peerreviewed reports that attest to deterioration of mental health due to the COVID-19 pandemic (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, the current report does not provide an in-depth review of this material due to concern expressed by others (25,26) that some of these data may be misleading due to not having been appropriately peer-reviewed.…”
Section: Introductionmentioning
confidence: 96%
“…In the same vein, the newness and the unknown of the Covid-19 pandemic together with the instantaneous changes in mortality statistics may affect individuals' mental well-being leading to heightened fear, worry, and stress (World Health Organization 2020c). Indeed, early evidence suggests that the Covid-19 outbreak has triggered anxiety and influenced mental well-being negatively (Adams-Prassl et al 2020; Davillas and Jones 2020).…”
Section: Introductionmentioning
confidence: 99%